Hypertrophic post‐acne scarring is associated with a single nucleotide polymorphism (rs243865) in the matrix metalloproteinase‐2 gene. (29th December 2020) - Gupta, Navya; Bishnoi, Anuradha; Mathew, Don; Arora, Amanjot; Handa, Sanjeev; Kaur, Jyotdeep; De, Dipankar; Pal, Arnab
Summary: Background and Objective: Aberrant tissue expression of matrix metalloproteinases has been observed in acne. Our objective was to study the relevance of MMP‐2 (‐1306 C/T, rs243865) and TIMP‐2 (‐418 G/C, rs8179090) single nucleotide polymorphisms (SNP) in acne and post‐acne scarring. Patients and methods: 512 patients (169 having acne without scarring, 319 having atrophic acne scarring, 24 having hypertrophic acne scarring) and 161 age‐matched controls were recruited from the Dermatology Outpatient Department after obtaining informed written consent. Venous blood (5 ml) was collected for genotyping by Polymerase Chain Reaction (PCR)‐Restriction Fragment Length Polymorphism (RFLP) method. The severity of acne and acne‐scarring were graded. Results: Males had a significantly increased risk of developing severe acne ( P = 0.012), extra‐facial acne ( P = 0.047) and extra‐facial acne scarring ( P = 0.0001). The presence of inflammatory acne positively correlated with severity of scarring ( P = 0.001). Subjects with a homozygous CC genotype of MMP‐2 (‐1306 C/T) had 1.0, 7.8 and 8.2 times the odds of developing hypertrophic scarring when compared to controls ( P = 0.05, 95 % CI: 0.7–1.6), subjects having acne without scarring ( P = 0.047, 95 % CI: 1.0–59.9) and subjects having atrophic scarring, respectively ( P = 0.041, 95 % CI: 1.1–59.9). Conclusions: A significant association was observed between hypertrophic post‐acne scarring and the CC genotype of MMP‐2 (‐1306 C/T) .